The effectiveness of an electronic training program to develop the skills of designing presentations according to Mayer standards among faculty members at Common First Year, King Saud University - Al-Shalan, Anas Mohammed (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to reveal the effectiveness of an electronic training program to develop the skills of design presentations according to Mayer standards among faculty members at Common First Year, King Saud University. And preparing a list of presentation design skills, and the experimental approach with a quasi- experimental design: in selecting the research group, controlling the variables, and performing statistical treatments for the data and research results in order to verify the validity of the research hypotheses and reach the appropriate statistical decision regarding them. The research sample consisted of (46) faculty members The results of the research indicated that there were statistically significant differences between the mean scores of the members of the experimental group and the control group in the post application of the achievement test for some cognitive aspects of the skills of designing presentations in the light of Mayer criteria in favor of the scores of the members of the experimental group. The results also indicated that there are statistically significant differences between the averages of The scores of the members of the experimental group and the control group in the post- application of the performance aspects note card A score of presentations design skills in the light of Mayer's criteria In favor of the scores of the faculty members in the experimental group.
Keywords: skills of design presentations; Mayer's principles